Complete mitochondrial DNA sequence of Pseudogastromyzon changtingensis (Osteichthyes: Gastromyzontidae). Issue 1 (1st January 2016) - Yang, Yang; Song, Xiaojing; Tang, Wenqiao
Abstract: Pseudogastromyzon changtingensis belonging to the family Gastromyzontidae is a good model for phylogeny and zoogeography research. In the present paper, the sequenced mitochondrial genome of P. changtingensis is of 16573 bp in length, and encodes 13 typical protein-coding genes, two ribosomal RNA genes, 22 transfer RNA genes, and one control region. The result of phylogenetic analysis demonstrates that P. changtingensis is close to that of P. fasciatus .